A Novel Loss-of-Function Mutation in the NPRL3 Gene Identified in Chinese Familial Focal Epilepsy with Variable Foci - Li, Youzhi; Zhao, Xu; Wang, Shanshan; Xu, Ke; Zhao, Xin; Huang, Shanshan; Zhu, Suiqiang (Frontiers in Genetics, 2021)
Familial focal epilepsy with variable foci is an autosomal dominant disorder characterized by partial epilepsy with variable foci. In this study, we report a six-generation with segregation of the mutation present in four generations Chinese family presenting with focal epilepsy with variable foci (FFEVF). The whole exome sequencing confirmed a novel pathogenic mutation in the NPRL3 gene (c316C>T; p. Q106*). PCR, western blotting and Immunohistochemistry were conducted to analyze the gene transcription, protein expression, and subcellular localization of NPRL3 and related signaling molecules in peripheral blood cells from family members. As compared to healthy family members, both mRNA level and protein expression of NPRL3 are decreased in peripheral blood cells of the mutation carrier. In addition, the expression of downstream molecular Phospho-p70 S6 Kinase（P-s6k）are increased consequently. Our findings expanded the genotypic and phenotypic spectrum of the NPRL3 associated epilepsy, and revealed the mechanisms of mTOR pathway signaling and GATOR1 pathogenesis in focal epilepsies, providing exciting potentials for future diagnostic and therapeutic interventions. However, further in vitro and animal experiments are still needed to evaluate the role of NPRL3 loss-of-function mutation in epileptogensis.